Ethical challenges and moral distress among field epidemiologists - Emma Cooke; George Lopez; Angela Hilmers; David G. Addiss (BMC, 2022)
Abstract Background As 'disease detectives' and directors of public health programs, field epidemiologists play essential roles in protecting public health. Although ethical issues receive considerable attention in medical and research settings, less is known about ethical challenges faced by field epidemiologists in public health programs. Similarly, little is known about moral distress among field epidemiologists, i.e., situations in which they are constrained from acting on what they know to be morally right. Moral distress is strongly associated with empathy fatigue, burnout, reduced job retention, and disengagement. To better understand ethics training needs for field epidemiologists, in February 2019, members of TEPHIConnect, an online and mobile networking platform for Field Epidemiology Training Program (FETP) alumni, were invited to participate in an anonymous survey about ethical challenges and moral distress. Results Among 126 respondents from 54 countries, leading causes of ethical dilemmas included inadequate informed consent (61%), inequitable allocation of resources (49%), and conflicts of interest (43%). These occur primarily in settings of disease outbreaks (60%); research (55%); and public health programs at the state, province, or national level (45%) or community level (43%). Work-related moral distress was reported by 91% of respondents, including 26% who experience it "frequently" or "almost always." Field epidemiologists working in low- and low-middle income countries were more likely to report moral distress "frequently" or "almost always" than those in higher-income countries (33.0% vs 9.1%, P = 0.006). The most common perceived contributors to moral distress included excessive stress and work demands (30%) and inadequate support from leaders (25%). Conclusions Field epidemiologists face significant work-related ethical challenges, which are endemic to public health and political systems. A substantial proportion of field epidemiologists also experience some degree of moral distress, often in association with these challenges. These findings indicate an unmet need among field epidemiologists for support in navigating ethical challenges, as well as for resources to address the human and professional consequences of moral distress.